Digital Transformation of Culinary Msmes in South Tangerang: The Impact of Social Media and Technology Adoption on Business Performance and Regional Income - Iin Andrayanti; Ambarwati Ambarwati; Lisa Arisa Fiatri (Eduvest - Journal of Universal Studies, 2026)
Digital transformation has become a key driver in the post-COVID-19 era for improving the competitiveness and performance of micro, small, and medium enterprises (MSMEs), including the rapidly growing culinary sector in urban areas such as South Tangerang City. The development of digital technology—particularly social media and e-commerce—offers significant opportunities for culinary MSMEs to reach a wider market, enhance operational efficiency, and contribute to regional income growth. This study aims to analyze the influence of social media and technology implementation on the performance of culinary MSMEs and their contribution to the Pendapatan Asli Daerah (PAD) of South Tangerang City. The research employed a mixed-methods sequential explanatory approach, combining a quantitative survey of 150 culinary MSMEs with in-depth interviews involving business owners and local government officials. The analysis results show that the use of social media significantly enhances marketing and consumer interaction, while the adoption of digital technologies—such as the Qasir application, e-commerce platforms, and digital payment systems—has a dominant influence on improving operational efficiency, productivity, and business turnover. These findings confirm that the success of digital transformation among culinary MSMEs in South Tangerang is influenced not only by internal factors but also by digital literacy, infrastructure, and government policy support. This study proposes a conceptual model of the digital transformation of culinary MSMEs that contributes to business growth and strengthens the regional fiscal base through increasing Regional Original Income.